2006
DOI: 10.1111/j.1525-1438.2006.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine computerized tomography scanning, groin ultrasound with or without fine needle aspiration cytology in the surgical management of primary squamous cell carcinoma of the vulva

Abstract: We set out to study whether computerized tomography (CT) scanning of the vulva and the groin and groin ultrasound scanning (USS) alone or with fine needle aspiration cytology (FNAC) (USS/FNAC) influenced or could influence the surgical management of primary squamous cell carcinoma of the vulva (SCCaV). Forty-four patients underwent surgery for primary SCCaV following radiologic imaging by one or more modalities. Patient details included the clinical assessment of the carcinoma, radiologic findings, the operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 24 publications
1
39
0
4
Order By: Relevance
“…However, in some cases CT confirmed regional tumor spread found at the gynecological examination. This is in accordance with a retrospective study, which could not recommend a CT scan in the preoperative examination of vulvar carcinoma, due to low sensitivity and specificity in the diagnosis of lymph node metastases [11]. Preoperative palpation of the groin [15] and other imaging modalities, such as PET/CT [8, 9] and MRI [10], have also shown to be inaccurate in the detection of inguinal lymph node metastases.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, in some cases CT confirmed regional tumor spread found at the gynecological examination. This is in accordance with a retrospective study, which could not recommend a CT scan in the preoperative examination of vulvar carcinoma, due to low sensitivity and specificity in the diagnosis of lymph node metastases [11]. Preoperative palpation of the groin [15] and other imaging modalities, such as PET/CT [8, 9] and MRI [10], have also shown to be inaccurate in the detection of inguinal lymph node metastases.…”
Section: Discussionsupporting
confidence: 73%
“…Outside Denmark, these supplementary cross-sectional imaging modalities are recommended routinely [6, 7]. However, the literature is scarce regarding the benefit of these preoperative examinations for the decisive surgical procedure and the final outcome of the patients, including identification of lymph node metastases and probable comorbidity and incidental findings detected [811]. The final stage of the disease is determined by the combined gynecological, pathological and radiological findings, in accordance to the revised guidelines proposed by the International Federation of Gynecology and Obstetrics (FIGO) [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…In a single institution study of 44 vulvar cancer patients, ultrasound with FNAC has shown high sensitivity and specificity of 80 and 100%, respectively, with FNAC being performed in each groin on the largest or most abnormal looking lymph node [12]. Computed tomography (CT) scanning performed less well with a sensitivity of 58% and specificity of 75% in this same group of patients [12]. The use of MRI for determining inguinal node status has shown a sensitivity of 52-87% and a specificity of 85-89% [13,14 ].…”
Section: Preoperative Imaging Of the Groinsmentioning
confidence: 99%
“…Typical ultrasound features are increase in size (e.g., > 5 mm in short-axis diameter), rounded shape, irregular contour, and loss of the fatty hilum. Ultrasound-guided fine-needle aspiration can help with proving nodal metastatic disease [4042]. …”
Section: Vulvar Cancermentioning
confidence: 99%
“…CT provides information on the presence of pelvic lymphadenopathy and distant metastases with a sensitivity and specificity of 58% and 75%, respectively [40]. …”
Section: Vulvar Cancermentioning
confidence: 99%